Internal derangement as a predictor of provoked pain on mouth opening: A magnetic resonance imaging study - Koh, Kwang-Joon; Park, Ha-Na; Kim, Kyoung-A (Imaging science in dentistry, 2017)
This study investigated the relationship between pain and internal derangement in temporomandibular disorder (TMD) patients using magnetic resonance imaging (MRI). This study analyzed 356 TMD patients (712 temporomandibular joints [TMJs]). The inclusion criteria were the presence of spontaneous or provoked pain on one or both TMJs and having undergone MRI. The patients with provoked pain were divided into 3 groups: pain on palpation, pain on mouth opening, and pain on mastication. MRI was performed using a 1.5-T scanner. T1- and T2-weighted parasagittal and paracoronal images were obtained. According to the findings on the T1-weighted images, another 3 groups were created based on internal derangement: normal, disc displacement with reduction, and disc displacement without reduction. The MRI findings were independently interpreted by 2 experienced oral and maxillofacial radiologists at 2 different times. Statistical analysis was performed by the chi-square test using SPSS (version 12.0; SPSS Inc., Chicago, IL, USA). Provoked pain on mouth opening was found to be correlated with internal derangement in TMD patients ( <.05). However, spontaneous pain and provoked pain on palpation or mastication were not associated with internal derangement ( >.05). These results suggest that internal derangement was a significant predictor of provoked pain on mouth opening.